Radionuclide release and transport from nuclear underground tests performed at Mururoa and Fangataufa — predictions under uncertainty - Pfingsten, Wilfried; Hadermann, Jörg; Perrochet, Pierre (My University, 2001)
In the context of a study by the International Geomechanical Commission (IGC) and the International Atomic Energy Agency (IAEA) on the effects of nuclear tests at the atolls of Mururoa and Fangataufa, release to the biosphere is estimated for 35 radionuclides originating from 147 nuclear underground tests. Based on a qualitatively characterised hydrogeological situation of atolls and relatively scarce site-specific data, a model chain was developed to conservatively estimate the radionuclide fluxes via groundwater, from their sources, the explosion cavities, towards the biosphere, the ocean or lagoon.
Finite element hydro-thermal modelling was used to describe water flow. Parameters were calibrated by a very few measured pre-test temperature profiles in bore holes. The impact of the tests on groundwater flow and mechanical impact on rock was considered. Estimates were made to quantify spatial extensions and temporal evolution of impact by using measurements on refilling rate of the cavities. Tests were categorised according to their specific yield and location although detailed data were missing. A base case parameter set was defined for the hydraulic conditions and for the initial radionuclide inventory of individual tests. Models were used to describe the concentration of radionuclides in the cavities as a function of time. Radionuclide transport from the cavities to the biosphere was represented by two different approaches: a double porosity model for the fractured volcanic rock and a single porosity model for the overlaying, highly porous carbonates. Results consist of conservative estimates on radionuclide release into the environment, or concentration in the lagoon or ocean water. Their sensitivity was investigated using different models and parameters. A few measured data (concentrations in a few cavities, in the deep carbonates and in the lagoons for selected radionuclides, such as 3H, 14C, 36Cl, 90Sr, 129I, 137Cs239, 240Pu and 241Am) were available for a comparison with the calculations. In view of the lack and uncertainty of site-specific data, the agreement is of acceptable quality.
Keywords: Mururoa atoll; Hydrogeologic modelling; Radionuclide transport; Nuclear tests; Data uncertainty